Recent Advances in the Synthesis and Modification of Carbon-Based 2d Materials for Application in Energy Conversion and Storage - Singh, D (Elsevier Ltd, 2018)
Graphene, reduced graphene oxide (rGO) and derived materials have emerged as promising solutions for applications in renewable energy storage/conversion devices. No alternatives are known to simultaneously exhibit large specific surface area, high electrical conductivity, good chemical stability, high mechanical strength and flexibility. This review article is a collection of some of the most relevant research efforts published in the last few years focusing on the synthesis and modification of graphene/rGO as well as doped and hybrid bi-dimensional carbon materials. For research on graphene growth, the choice of precursor and physical state (gas, solid or liquid) has been proved to be as important as the environment and synthesis approach. On the other hand, research focused on graphene oxide reduction has relied on the development of simple and efficient techniques for rGO conversion and device structuring. Modifications applied to graphene (during synthesis) or rGO (during reduction) have included doping, decoration with nanoparticles and the formation of composite microstructures. Fabrication of electrodes based on graphene/rGO for application in energy storage and conversion has been reported, including relevant performance data from real devices (supercapacitors, lithium ion batteries, fuel cells or solar cells). This review concludes with a brief discussion of some of the possible directions for promising research in the area of graphene/rGO fabrication for energy conversion and storage devices. © 2018 Elsevier Ltd